2018
DOI: 10.1126/science.aas9699
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution cryo-EM analysis of the yeast ATP synthase in a lipid membrane

Abstract: Mitochondrial ATP synthase comprises a membrane embedded Fo motor that rotates to drive ATP synthesis in the F1 subunit. We used single-particle cryo-EM to obtain structures of the full complex in a lipid bilayer in the absence or presence of the inhibitor oligomycin, at 3.6 Å and 3.8 Å resolution, respectively. To limit conformational heterogeneity, we locked the rotor in a single conformation by fusing the F6 subunit of the stator with the δ-subunit of the rotor. Assembly of the enzyme with the F6-δ fusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
214
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(226 citation statements)
references
References 58 publications
11
214
1
Order By: Relevance
“…The structure of the yeast ATP synthase FO dimer 12 , which lacked the the F1 region and an intact peripheral stalk, showed that the c-ring and subunit a are held together by hydrophobic interactions rather than by the peripheral stalk. In Bacillus PS3 ATP synthase, the peripheral stalk is structurally simpler and more flexible than in yeast mitochondria 14 , suggesting that the bacterial subunits a and the c-ring are also held together by hydrophobic interactions and not the peripheral stalk. Given that these structures represent resting states of the bacterial ATP synthase, additional subunits, such as those in the central stalk, may show flexibility while under strain during rotation.…”
Section: Flexibility In the Peripheral And Central Stalksmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the yeast ATP synthase FO dimer 12 , which lacked the the F1 region and an intact peripheral stalk, showed that the c-ring and subunit a are held together by hydrophobic interactions rather than by the peripheral stalk. In Bacillus PS3 ATP synthase, the peripheral stalk is structurally simpler and more flexible than in yeast mitochondria 14 , suggesting that the bacterial subunits a and the c-ring are also held together by hydrophobic interactions and not the peripheral stalk. Given that these structures represent resting states of the bacterial ATP synthase, additional subunits, such as those in the central stalk, may show flexibility while under strain during rotation.…”
Section: Flexibility In the Peripheral And Central Stalksmentioning
confidence: 99%
“…The architecture of the membrane region shows how the simple bacterial ATP synthase is able to perform the same core functions as the equivalent, but more complicated, mitochondrial complex. The structures reveal the path of transmembrane proton translocation and provide a model for understanding decades of biochemical analysis interrogating the roles of specific residues in the enzyme.structures of the membrane-embedded FO regions from mitochondrial and chloroplast ATP synthases to be determined to near-atomic resolutions [12][13][14][15] .Compared to their mitochondrial counterparts, bacterial ATP synthases have a simpler subunit composition. The F1 region consists of subunits a3b3gde, while the FO region is usually formed by three subunits with the stoichiometry ab2c9-15.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One method is to use lipid nanodiscs, where the membrane protein resides in a small patch of lipid bilayer encircled by an amphipathic scaffolding protein (Bayburt et al, 2002). The nanodisc method has been employed to study the anthrax toxin pore at 22-Å resolution (Katayama et al, 2010), TRPV1 ion channel in complex with ligands at 3-4 Å resolution (Gao et al, 2016), and other membrane proteins (Autzen et al, 2018;Bayburt et al, 2002;Chen et al, 2017;Dang et al, 2017;Gao et al, 2016;Jackson et al, 2018;Katayama et al, 2010;McGoldrick et al, 2018;Roh et al, 2018;Srivastava et al, 2018;Taylor et al, 2017). Another method, called "random spherically constrained" (RSC) single-particle cryo-EM, where the membrane protein is reconstituted into liposomes, was developed and employed to study the large conductance voltage-and calcium-activated potassium (BK) channels reconstituted into liposomes at 17-Å resolution (Wang and Sigworth, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on open time and channel size, PTP/MMC activity can contribute to Ca 2+ homeostasis (short-term and/ or low conductance openings) or cell death (long-lasting high conductance openings) [1], but a molecular explanation for this complex behaviour has not been provided yet. Available structures of F-ATP synthase do not display obvious channel-like structural features [7][8][9][10][11] and therefore whether and how the enzyme can form the PTP remains debated. In spite of these open questions, the site of action of several PTP modulators is now being traced to specific residues of F-ATP synthase.…”
Section: Introductionmentioning
confidence: 99%